IMPLEMENTASI KEBIJAKAN PERLINDUNGAN ANAK DARI TINDAK KEKERASAN DI KOTA BANDUNG - Widya Dana, Azaria; Lituhayu, Dyah; Larasati Setianingsih, Endang (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Violence against children is a serious legal and moral issue that causes both physical and psychological suffering. Bandung City faces a high and fluctuating number of child violence cases annually. The Department of Women's Empowerment and Child Protection (DP3A) in Bandung City is tasked with addressing this issue, guided by the Bandung City Regional Regulation No. 4 of 2019. This study examines the implementation of child protection policies against violence in Bandung City, using Van Meter and Van Horn's policy implementation theory. A qualitative research method was employed, utilizing interviews and observations with purposive and snowball sampling techniques. The findings reveal that the policy implementation includes prevention, risk reduction, response, data information systems, and role enhancement of involved parties. However, challenges persist, particularly in risk reduction, due to the absence of a violence distribution map. Key obstacles include limited human resources, budget constraints, and inadequate communication and coordination among stakeholders. Nevertheless, clear policy standards, committed implementers, and supportive organizational characteristics serve as driving factors. The study recommends that DP3A and UPTD PPA strengthen institutional capacities, improve communication, conduct violence mapping, and enhance the community-based Child Protection and Welfare Monitoring (PATBM) system comprehensively.